Comparison between the effects of high sevoflurane concentration during induction of anasesthesia using vital capacity breath and tidal breathing techniques in adults - Lim, K. Y.; Wong, Wai Hong; P. Shanmugam, Suresh Kumar; Ibrahim, Noor Airini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2009)
Introduction: The aims of this randomised study were to compare the induction characteristics of sevoflurane using vital capacity breath technique to that of tidal breathing technique in adults undergoing day-care surgery, and to compare patients’ acceptance of these two techniques. Methods: Sixty ASA I and II adult patient undergoing day-care surgery were randomly allocated to receive either the vital capacity breath or tidal breathing technique for induction of anaesthesia with 7.5% sevoflurane in nitrous oxide and oxygen. Haemodynamic changes, induction characteristics and patients acceptance were compared. Results: The mean time for induction was significantly faster with the vital capacity breath technique. There were no significant differences in haemodynamic changes and oxygenation during induction between these two groups. There was significant increase in incidence of excitatory movement in patient receiving the tidal breathing technique. Either technique was found to be acceptable by most of the patients studied. Conclusion: The vital capacity breath technique appears to be better tolerated with shorter onset time and less movement during induction of anaesthesia. As it is well accepted by the patients and has a stable haemodynamic profile, its use should be encouraged.